Synopsis: Improving agricultural productivity in Papua New Guinea: Strategic and policy considerations - Benny, Dickson; Benson, Todd; Ivekolia, Mark; Kedir Jemal, Mekamu; Ovah, Raywin (International Food Policy Research Institute, 2022)
In a recent working paper, we examine staple and cash crop production yields in Papua New Guinea (PNG). In doing so, we assess the yield gap (difference between the crop yields farmers commonly obtain and what they might realize with optimal inputs and crop management) for the main staple food crops in PNG. The yield gap for sweet potato is the smallest (1/4 - 1/3 less than attainable yields), while banana shows the largest yield gap at about ¾ less than what might be achieved under intensive cultivation. In addition, we compare PNG agricultural output with areas of similar growing conditions in Indonesia to provide insight into potential investments to further spur agricultural productivity in PNG. Finally, we assess current sector policies in PNG that aim to support agricultural development as an engine for economic growth.